Elektrokoagulasi Kontinu (CEC) untuk Tujuan Pembangunan Berkelanjutan - Vera Cerelia Yolanda; Sudarno; Nurandani Hardyanti; Bimastyaji Surya Ramadan (Jurnal Penelitian Pendidikan IPA, 2026)
Wastewater treatment requires effective technologies for pollutant removal and sustainable water management. This study aimed to map the development of Continuous Electrocoagulation (CEC) research, identify research gaps and emerging themes, and synthesize operational and implementation issues. A Systematic Literature Network Analysis (SLNA) integrating Bibliometric Analysis (BA) and Qualitative Content Analysis (QCA) was applied to 99 Scopus-indexed journal articles published between 2019 and 2024. BA examined publication trends, collaboration networks, and research hotspots, while QCA synthesized evidence on Sustainable Development Goals (SDGs), operational factors, and implementation challenges. Publication output increased from 7 articles in 2019 to a peak of 22 in 2022, followed by 20 in 2023 and 14 in 2024. Thematic analysis indicated increasing attention to continuous operation, reactor configuration, pollutant removal, and energy efficiency. QCA showed that CEC research repeatedly examines electrode material, current density, pH, electrode distance, flow rate, electrolysis time, conductivity, temperature, supporting electrolytes, and hydraulic retention time. Key implementation challenges include electrode passivation, energy and electrode consumption, sludge management, effluent-quality control, and limited reactor standardization and scale-up evidence. Overall, CEC shows potential to support SDGs, while future research should prioritize multivariable optimization, pilot-scale validation, and sustainability assessment.